PHYLOGENY OF EARLY CRETACEOUS SPATANGOIDS (ECHINODERMATA: ECHINOIDEA) AND TAXONOMIC IMPLICATIONS - Villier L.; Neraudeau D.; Clavel B.; Neumann Ch.; David B. (My University, 2004)
A phylogenetic analysis of 36 species provides a test for the taxonomy and the history of Early Cretaceous spatangoids. Most taxonomic units from genera to suborders are consistent with the proposed phylogenetic framework. We retain Hemiasterina, Micrasterina, Hemiasteridae, Schizasteridae, Hemiaster, Heteraster, Mecaster, and Periaster as original monophyletic groups. However, all of these clades originate without the classical apomorphies normally ascribed to them. We suggest a revision of their diagnoses and of the generic attributions of basal species. Some ill-defined, 'primitive', and paraphyletic taxa are recognised: Toxaster, Epiaster, Palhemiaster, and Toxasteridae. Even if they do not have phylogenetic meaning, they are retained here, pending a more complete revision.
Keywords: SPATANGOIDA; ECHINOIDEA; PHYLOGENY; SYSTEMATICS; CRETACEOUS; Mesozoic::Cretaceous; Мезозой::Меловая